2020
DOI: 10.1002/jsfa.10599
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the biofumigant capacity of allyl isothiocyanate from several Brassicaceae crops against Fusarium pathogens in maize

Abstract: BACKGROUND: Driven by environmental concerns, chemical fumigants are no longer allowed in many countries. Therefore, other strategies for reducing fungal inoculum in soils and on crop debris are being explored. In the present study, several Brassicaceae crops were screened for their potential to control Fusarium gramineaum and Fusarium poae mycelial growth in an in vitro inverted Petri dish experiment. Volatile production was measured using gas chromatography-mass spectrometry headspace analysis. A selection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
1
8
0
2
Order By: Relevance
“…The most frequently used species are young plants of Brassica juncea , B. napus , B. rapa , B. oleracea , B. carinata and Sinapis alba . The results mainly include disease suppression of the plant of interest in several crop-pathogen pairs [ 48 , 49 , 74 , 75 , 104 , 113 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 ]. The studies include in vitro, pot and field studies as well, summarized in Table S3 .…”
Section: Biofumigation Inhibition Of Plant Pathogenesismentioning
confidence: 99%
“…The most frequently used species are young plants of Brassica juncea , B. napus , B. rapa , B. oleracea , B. carinata and Sinapis alba . The results mainly include disease suppression of the plant of interest in several crop-pathogen pairs [ 48 , 49 , 74 , 75 , 104 , 113 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 ]. The studies include in vitro, pot and field studies as well, summarized in Table S3 .…”
Section: Biofumigation Inhibition Of Plant Pathogenesismentioning
confidence: 99%
“…We found the Brassicaceae significantly reduced the abundance of potential plant fungal pathogens. Brassicaceae, and more specifically mustards, have been deemed ideal for biologically suppressing plant pathogens such as plant parasitic nematodes and fungal pathogens due to their production of glucosinolates and isothiocyanates [114][115][116][117][118][119][120][121][122]. However, it has also been shown that isothiocyanates produced by Brassica kaber and Brassica nigra inhibit mycorrhizal fungi [123].…”
Section: Soil Health: Linking Microbial Communities Agroecosystem Services and Crop Traitsmentioning
confidence: 99%
“…De acuerdo a lo expuesto por autores como Manici et al, (2004) y Mazzola (2010), dentro de la microbiota antagónica favorecida se encuentran bacterias como Bacillus, Pseudomonas y especies no patogénicas de Streptomyces, así como el hongo Trichoderma (Yossen et al, 2011), del hay especies con mayor tolerancia frente a isotiocianatos producidos por tejidos incorporados de Brassica, respecto a otros hongos patógenos del suelo (Larkin y Griffin, 2007;Vandicke et al, 2020). En este grupo de plantas, se ha identificado especies de mostaza como Brassica juncea y B. nigra poseen efecto biofumigante contra aislados del patógeno R. solani en papa y hortalizas (Rubayet et al, 2018;Abdallah, Yehia, y Kandil, 2020).…”
Section: Discussionunclassified
“…Se ha demostrado que especies de la familia Brassicaceae poseen componentes naturales como los glucosinolatos, producidos a partir del metabolismo secundario de las plantas que al ser utilizadas como abonos verdes liberan una serie de compuestos tóxicos, en especial la capacidad biofumigante de los isotiocianatos, que limitan directamente el desarrollo hongos patógenos del suelo (Larkin y Griffin, 2007;Vandicke et al, 2020). Dayegamiye et al, (2017), exponen que la incorporación al suelo de cereales como variedades de rápido crecimiento de cebada, avena o trigo, cuyo aporte considerable de biomasa trae consigo efectos positivos sobre las propiedades del suelo y su microbiota; condiciones que predisponen una menor incidencia de fitopatógenos.…”
Section: Introductionunclassified